Identification of Gene Resistance to Avian Influenza Virus (Mx Gene) among Wild Waterbirds - Elfidasari, Dewi; Solihin, Dedy Duryadi; Soejoedono, Retno Damayanti; Murtini, Sri (UI Scholars Hub, 2013)
The Mx gene is an antiviral gene used to determine the resistance or the susceptibility to different types of viruses, including the Avian Influenza (AI) virus subtype H5N1. The AI virus subtype H5N1 infection in chickens causes Mx gene polymorphism. The Mx+ gene shows resistant to the AI virus subtype H5N1, whereas the Mxgene shows signs of susceptible. The objective of this research was to detect the Mx gene in wild aquatic birds using the Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method with the primer pairs F2 and NE-R2/R and the RsaI restriction enzyme. DNA samples were obtained from eight species of wild waterbirds with positive and negative exposure to the AI virus subtype H5N1. DNA amplification results showed that the Mx gene in wild aquatic birds is found in a 100 bp fragment, which is the same as the Mx gene found in chickens. However, unlike chickens, the Mx gene in wild aquatic birds did not show any polymorphism. This study proves that Mx- based resistance to AI virus subtype H5N1 in different in wild birds than in chickens.